Perfil bioquímico sérico em potros Bretão Postier e cães Doberman em fase de crescimento e de cabras Saanen nos diferentes estádios de lactação - Mundim, Antonio Vicente (2008)
The growth of domestic animals and lactation in highly productive females are phases of life with special physiological characteristics and nutritional needs. Failure to adequately meet those needs may lead to negative effects on the animals physical development, productivity and performance. When interpreted correctly, the analysis of the biochemical serum profile of the individual animal or the herd is an effective tool for the detection of nutritional failures and imbalances, allowing for early corrective action to avoid impairing growth, productivity and performance. Its correct interpretation in animal species depends on specific regional reference values for the different phases of life, since various factors relating to both the animal and the environment may influence these values, leading to false results. In this context, the purpose of this study was to investigate the influence of age and sex on the biochemical serum profile of Postier Breton colts and on Doberman dogs in the growth phase, and the influence of the order and stages of lactation on the serum biochemistry of Saanen goats. In chapter 2, an analysis was made of 165 blood samples collected on five distinct occasions during a one-year period from 33 Postier Breton colts and fillies aged 9 days to 24 months. Greater activity of aspartate aminotransferase and creatine kinase enzymes was observed in the females, and age was found to influence the values of total proteins, albumin, globulins, A:G ratio, urea, uric acid, total cholesterol, total calcium, ionized calcium, phosphorus, Ca:P ratio, chlorides, alanine aminotransferase (ALT), aspartate aminotransferase (AST), γ-glutamyltransferase (GGT), alkaline phosphatase (ALP) and creatine kinase (CK). For the study on dogs in chapter 3, 132 blood samples were collected from 44 male and female Doberman dogs with ages ranging from 2 to 36 months. It was found that the mean values of most of the biochemical parameters of the dogs remained within the physiological intervals, and age was found to affect the serum concentrations of total proteins, albumin, globulins, A:G ratio, urea, creatinine, cholesterol, total calcium, ionized calcium, phosphorus, iron, ALT and ALP. The males presented a higher concentration of phosphorus and the females a higher Ca:P ratio. In chapter 4, an analysis was made of blood samples from 123 Saanen goats in the first, second and third period of lactation. The total proteins, glucose, triglycerides, total calcium, ionized calcium, AST and ALP values were found to be affected by both the order and the stages of lactation, while magnesium varied only between the phases of lactation. It was concluded that age influences the values of most of the biochemical serum parameters of Postier Breton colts and Doberman dogs, especially colts up to 12 months old and dogs up to 6 months old. The serum concentrations of glucose, triglycerides, total calcium, ionized calcium, magnesium, AST and ALP are effective biomarkers for the detection of energy and mineral imbalances in lactating goats. The results of this study may aid veterinary clinical pathologists in the interpretation of clinical biochemistry and in obtaining regional reference values.